Meta-Analysis the Effects of Loneliness on Depression in Elderly - Muhammad Zainul Arifin; Hasdianah Hasan Rohan (GLOBAL HEALTH SCIENCE GROUP, 2023)
The impact loneliness on health and well-being is recognized globally as a public health problem. Loneliness can be experienced at any age, especially in the elderly. This study aimed to analyze and estimate the influence of loneliness on depression in the elderly. This type of research is meta-analysis and was carried out according to the PRISMA flow chart and the PICO model. P: elderly, I: loneliness, C: not lonely, O: depression. Search for articles in this study through databases that include PubMed, ProQuest, and Springer Link with keywords